A Correlational Study of the Bahtsul Masail Method, Learning Motivation, and Students’ Understanding of Islamic Law - Husnawadi, Husnawadi (AS-SABIQUN, 2025)
This study addresses the limited empirical investigations into the correlation between traditional Islamic learning models and student academic outcomes in higher education, specifically within the context of Islamic legal education. The purpose of this research was to analyze the relationship between the Bahtsul Masail method, learning motivation, and students’ understanding of Islamic law among fourth-semester students in the Ahwal al-Syakhsiyah program at IAIH NW Lombok Timur. A quantitative correlational approach was employed, involving a purposive sample of 53 students. Data were collected utilizing validated questionnaires and comprehension tests on Islamic law, subsequently analyzed through descriptive statistics and Pearson’s Product-Moment Correlation. The findings indicated that the implementation of the Bahtsul Masail method (M=78.5), students' learning motivation (M=81.2), and their understanding of Islamic law (M=76.4) all fell within the "high" category. Notably, significant positive correlations were identified between: (1) the Bahtsul Masail method and understanding of Islamic law; (2) learning motivation and understanding of Islamic law; and (3) the Bahtsul Masail method and learning motivation. These results highlight the necessity of integrating traditional pedagogical methods with motivational strategies to enhance educational outcomes in Islamic law programs. The study contributes to constructivist learning theory and Nurhayati’s motivational framework, illustrating how collaborative, context-rich learning experiences can promote deeper legal comprehension and academic motivation. The implications extend to curriculum development, teacher training, and instructional design, balancing classical Islamic approaches with contemporary educational needs. Future research should investigate longitudinal impacts, utilize mixed methods, and encompass additional Islamic law faculties to further elucidate this pedagogical synergy.